TOWARDS INSTITUTIONALIZING INTERNATIONAL MEDIATION - Gashparova, Vassilena (Lex Electronica)

(untitled) (Centre de recherche en droit public Université de Montréal, 2023)
The obligation to settle international disputes through peaceful means is one of the most fundamental principles of international relations. A variety of dispute resolution mechanisms are at the disposal of states to resolve international disputes. Mediation is undoubtedly one of the most effective dispute-resolution means. However, unlike arbitration and adjudication, there is a lack of consistency in mediation approaches and standards of practice. A careful analysis of international disputes resolved in contemporary history reveals that the facilitators who purport to be mediators do not always comply with fundamental principles of mediation, namely independence, impartiality, and neutrality.This article calls for the institutionalization of international mediation through a permanent independent entity. It argues that institutionalizing mediation is the only way to achieve a reasonable degree of standardization of mediation practices and approaches. The proposed institutionalization will inevitably make mediation more accessible to disputing parties, resulting in a greater number of conflicts being settled through mediation. Institutionalization will also promote research and academic literature in international mediation, bringing about further professionalization of the field.The first part of this article draws a distinction between judicial dispute resolution mechanisms and diplomatic dispute resolution mechanisms, including mediation, which continues to evolve in an organic and unsystematic manner. The second part explores well-known international conflicts that have been successfully or unsuccessfully mediated by prominent individuals, namely the Secretary-General of the United Nations, Heads of state, religious leaders, and other dignitaries. The third and last part of the article makes a case that the UN, states, international organizations, religious leaders, and other prominent individuals are rarely, if ever, suitable mediators because they are not independent, impartial, or neutral for a variety of reasons. The logical conclusion to which the analysis leads is that it is high time to institutionalize international mediation by establishing a permanent independent entity entrusted with mediating international disputes.